Intérêt de la bave d’escargot dans le domaine cosmétique - Hachemi, Fatiha; Chachoua, Soaad (My University, 2024)
Our work made it possible to collect ingredients used in cosmetic recipes promoting skin distribution from natural raw materials. The biological activities of some natural extracts have been mentioned by users. The results of this investigation showed that the plant components are the most used, more precisely the aerial part with different extraction methods. To this end, our study will focus on the manufacture of soap based on a natural animal substance (snail slime). Additional studies, in particular the evaluation of effectiveness as well as toxicology tests, are necessary for better valorization of plants for cosmetic uses. Biodiversity is an abundant source of molecules of interest for designing natural active ingredients intended for cosmetics. This sector is governed by consumer demands for investigation of natural products with demonstrated effectiveness, to which formulators respond by integrating natural active ingredients
Keywords: Cosmetic products; natural substance; investigation; snail slime